Federal Practitioner 2021
DOI: 10.12788/fp.0177
|View full text |Cite
|
Sign up to set email alerts
|

Right Ventricle Dilation Detected on Point-of-Care Ultrasound Is a Predictor of Poor Outcomes in Critically Ill Patients With COVID-19

Abstract: Background: During the COVID-19 pandemic, the need for judicious use of diagnostic tests and to limit personnel exposure has led to increased use and dependence on point-ofcare ultrasound (POCUS) examinations. We reviewed POCUS findings in patients admitted to the intensive care unit (ICU) for acute respiratory failure with COVID-19 and correlated the findings to severity of illness and 30-day outcomes. Methods: Patients admitted to the ICU in March and April 2020 were reviewed for inclusion (acute hypoxemic r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 19 publications
0
5
0
1
Order By: Relevance
“…There are similar retrospective studies that observed LUS's utility in monitoring patients with PaO2/FiO2 ratio <200 mmHg. Patients with a major LUS score value correlated with a worse outcome [42], or in a specular way, worse PaO2/FiO2 ratio correlated with worse LUS findings [43]. This kind of correlation was also observed for intubated patients [44].…”
Section: Prognostic Stratification and Monitoringmentioning
confidence: 58%
“…There are similar retrospective studies that observed LUS's utility in monitoring patients with PaO2/FiO2 ratio <200 mmHg. Patients with a major LUS score value correlated with a worse outcome [42], or in a specular way, worse PaO2/FiO2 ratio correlated with worse LUS findings [43]. This kind of correlation was also observed for intubated patients [44].…”
Section: Prognostic Stratification and Monitoringmentioning
confidence: 58%
“…For the purposes of this discussion, we have selected and tabulated ( Table 5 ) prior relevant reports where there was sufficient data for between-study comparisons, including RV dysfunction, need for mechanical ventilation, and mortality rates. 2 , 11 , 12 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 To simplify the comparison between our study and the previously published reports, prior studies were sorted by the reported hospital mortality. Accounting for differences in study populations and reported endpoints, our findings agree with prior reports.…”
Section: Discussionmentioning
confidence: 99%
“… In the studies with available data endpoints, including current one (star), visual assessment reveals strong positive correlation between RV dilatation and mortality (Panel A), RV dilatation and positive pressure ventilation (Panel B), and positive pressure ventilation and mortality (Panel C). 2 , 11 , 12 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 …”
Section: Discussionmentioning
confidence: 99%
“…Early in the COVID-19 pandemic data appeared indicating right ventricular strain and remodeling, as well as heterogenous pulmonary perfusion and pulmonary vascular remodeling, in patients with COVID-19 9,38,39 . Furthermore, reports showed the emergence of PH in patients who had no prior history of lung vascular disease 7,9 .…”
Section: Discussionmentioning
confidence: 99%